COBRA. Season two : Cyberwar, [videorecording (DVD)] - Carlyle, Robert, 1961-; Hamilton, Victoria, 1971-; Dormer, Richard, 1969-; Haig, David; Thomason, Marsha, 1976-; Cohu, Lucy, 1970-; Palfrey, Lisa; Bennett, Edward, 1979-; Pepple, Richard; Davies, Alexa, 1995- (PBS Distribution, 2022)
In times of national emergency, a team of Britain's leading experts, crisis contingency planners and most senior politicians from the corridors of Whitehall to the salons of No. 10 Downing St. assemble under the name COBRA to coordinate the response.